Merkel Cell Carcinoma of Skin-Case Report with Literature Review - د.صفاء قطليش Qatleesh; د.فريز أحمد (مجلة جامعة دمشق للعلوم الطبية, 2023)
Background & Aim: Merkel cell carcinoma is a rare, very aggressive malignancy of the skin with a poor prognosis. It is typically located on sun-exposed skin.